Green Pathways: From Environmental Strategies and Green Intellectual Capital to Environmental Performance, with the Mediating Role of Environmental Management Accounting - Amir, Muhammad; Uddin, Moin; Shaukat, Hafiza Safia; Khan, Sadaf; Arshad, Saira; Ansari, Mahnoor; Arshad, Amna (Journal of Environmental Accounting and Management, 2026)
Organizations are increasingly focusing on environmental sustainability as a crucial aspect of their operations in pursuit of sustainable development goals. This study investigates the influence of environmental strategies and green intellectual capital on environmental performance, while considering the mediating effect of environmental management accounting. Data were gathered through self-administered questionnaires from 411 manufacturing organizations in Pakistan. The analysis was conducted using SPSS and AMOS software, employing structural equation modelling to test the study hypotheses. To the best of our knowledge, this study breaks new grounds by offering a comprehensive examination of the relationship among environmental strategies, green intellectual capital, and environmental performance, particularly within manufacturing organizations with ISO 14001 certification, emphasizing the critical role of environmental management accounting as a mediator. Drawing from the natural resource orchestration approach, this study offers valuable insights for managers and shareholders, emphasizing the significance of strategic environmental management and intellectual capital in achieving long-term sustainability objectives beyond financial gains.